Phytochemical screening and in vitro antioxidant potential of hydroalcoholic extract from the aerial parts of bryonopsis laciniosa - LENIN BABU VALLURI; Dr. K. S. MURALI KRISHNA; CH. MADHU (International Journal of Pharma and Bio Sciences, 2017)
The aim of present study was to estimate the total phenolic and flavonoid content and also to evaluate in-vitro antioxidant potential of hydroalcoholic extract of aerial parts of Bryonopsis laciniosa (HAEBL). Antioxidant activity was assessed by using 2, 2- diphenyl-1-picryl-hydrazyl (DPPH) assay, ferric reducing power, Hydrogenperoxide radical scavenging assay, nitric oxide scavenging assay, superoxide radical scavenging assay and hydroxyl radical scavenging assay using ascorbic acid as standard antioxidant. The data obtained from all these models clearly suggested that the antioxidant activity of HAEBL was significant and dose dependent. The extract was found to scavenge effectively the free radicals such as peroxides, superoxides and hydroxyl radicals. The total phenolic and flavonoid contents were determined by established methods and were found to be 126.1 mg GAE/g and 262.6 mg of CE/g in gallic acid and catechin equivalents respectively. The antioxidant activities may be attributed to the presence of significant amounts of phenolic and flavonoid compounds.